Analyses of prevalence and molecular typing reveal the spread of antimicrobial-resistant Salmonella infection across two breeder chicken farms. (17th July 2018) - Fei, Xiao; Yin, Kequan; Yin, Chao; Hu, Yachen; Li, Jingwen; Zhou, Zihao; Tian, Yuqi; Geng, Shizhong; Chen, Xiang; Pan, Zhiming; Li, Qiuchun; Jiao, Xinan
ABSTRACT: In this study, Salmonella prevalence and antimicrobial resistance were evaluated at various production stages in 2 geographically separated breeder farms (referred to as G and F). Day-old chicks for the breeder flock at farm F were purchased from farm G. A total of 219 Salmonella isolates, all identified as Salmonella enterica subsp. enterica serovar Enteritidis, were recovered from 1, 430 samples (sick chicken carcasses and/or dead embryos). The isolation rates at breeder farms G and F were 10.53% (56/532) and 18.15% (163/898), respectively. Resistance to 4–6 antimicrobial agents was the most frequent phenotype during the laying stage at both farms, suggesting that chicks are exposed to higher risk of antimicrobial-resistant Salmonella infection during this stage of the breeding process. Using clustered regularly interspaced short palindromic repeat (CRISPR) typing, 5 CRISPR patterns were identified, out of which one pattern was shared by the 2 farms. In addition, pulsed-field gel electrophoresis (PFGE) typing result indicated that 2 clusters (PF-1 and PF-2) were shared among the 2 breeder farms, suggesting that strains were transmitted from breeder farm G to farm F via the trade of day-old chicks. Our findings suggested that the trade of day-old breeder chicks could be one of the potential Salmonella transmission routes, and antibiotics should be administered with caution during the laying stage.